Information and Communication Technologies for the Civic Participation of Parents in Schools: A Systematic Review - Tello-Flores, Braulio; López-Regalado, Oscar (International Journal of Engineering Pedagogy (iJEP), 2024)
The Internet has become a space where parents share their parenting experiences. However, citizenship education requires digital skills that go beyond the simple critical ability to evaluate virtual information and understand its relevance. This paper is a systematic literature review that examines the progress of parents’ citizenship participation in schools through information and communication technologies (ICT) over the period from 2016 to 2024. The study adopts a bibliometric approach and follows the guidelines of the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement. It analyzes 50 articles in the context of the PRISMA declaration. It focuses on three main aspects: the panoramic vision of digital citizenship, the semantic connection between groups of interconnected terms, and the role of parents in shaping citizenship. The results reveal a notable 31.61% increase in parents’ civic participation in school, identifying parents’ expectations in their children’s learning as well as students’ civic participation in school, highlighting the use of digital technologies to foster collaborative and academic learning in the construction of ICT-mediated citizenship.